1985
DOI: 10.1093/jaoac/68.5.811
|View full text |Cite
|
Sign up to set email alerts
|

Sample Preparation for Chromatography of Amino Acids: Acid Hydrolysis of Proteins

Abstract: A number of variations were evaluated in the techniques and procedures of the classical 6N hydrochloric acid, 110°C, 24 h hydrolysis of protein. Variations included the use of glass tubes with Teflon-lined screw caps as the hydrolysis vessel, high-temperature short-time hydrolysis, performic acid oxidation of cystine and methionine, multiple hydrolysis times at 145°C, and interlaboratory preparation of hydrolysates. A diverse sample set used in the study included a range of protein-containing matrices, and aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 0 publications
1
93
0
Order By: Relevance
“…The samples of RSM and FRSM were ground, passed through a 60-mesh sieve, and then analyzed for crude protein, water-soluble protein, peptides, 9 water-soluble sugar, tannin, glucosinolates, phytic acid, 23 and crude fiber. The amino acid composition of RSM and FRSM was determined using an automatic amino acid analyzer (Agilent Technologies Inc., Santa Clara, CA, USA) after the samples had been hydrolyzed with 6 mol L −1 hydrochloric acid at 110°C for 24 h. 24 Electronic nose signal acquisition The electronic nose (FOX 3000; Alpha MOS, Toulouse, France) was equipped with 12 different gas sensors (LY2/LG, LY2/G, LY2/AA, LY2/GH, LY2/gCTL, LY2/gCT, T30/1, P10/1, P10/2, P40/1, T70/2, and PA/2) to analyze the volatile gas molecules using sensor array response and pattern recognition techniques. Samples of RSM (2.0 g) were placed in 20 mL sealed vials and then heated at 50°C for 10 min.…”
Section: Chemical Composition Analysis Of Rsm and Frsmmentioning
confidence: 99%
“…The samples of RSM and FRSM were ground, passed through a 60-mesh sieve, and then analyzed for crude protein, water-soluble protein, peptides, 9 water-soluble sugar, tannin, glucosinolates, phytic acid, 23 and crude fiber. The amino acid composition of RSM and FRSM was determined using an automatic amino acid analyzer (Agilent Technologies Inc., Santa Clara, CA, USA) after the samples had been hydrolyzed with 6 mol L −1 hydrochloric acid at 110°C for 24 h. 24 Electronic nose signal acquisition The electronic nose (FOX 3000; Alpha MOS, Toulouse, France) was equipped with 12 different gas sensors (LY2/LG, LY2/G, LY2/AA, LY2/GH, LY2/gCTL, LY2/gCT, T30/1, P10/1, P10/2, P40/1, T70/2, and PA/2) to analyze the volatile gas molecules using sensor array response and pattern recognition techniques. Samples of RSM (2.0 g) were placed in 20 mL sealed vials and then heated at 50°C for 10 min.…”
Section: Chemical Composition Analysis Of Rsm and Frsmmentioning
confidence: 99%
“…The amino acid profiles were determined using the HPLC Pico-Tag system according to the method previously described by Bidlingmeyer, Cohen, and Tarvin (1984) after samples were digested with 6 M HCl for 24 h. The cysteine and methionine contents were determined after performic acid oxidation (Gehrke, Wall, Absheer, Kaiser, & Zumwalt, 1985), and the tryptophan content was determined after alkaline hydrolysis (Landry & Delhaye, 1992).…”
Section: Determination Of Amino Acid Compositionmentioning
confidence: 99%
“…Although HPLC has been used in the study of amino acids, a review of published studies revealed that most of them have focused on the application of hydrolysis and previous treatment to protect CYS and MET in foods such as fish meal, maize corn meal, mixed feed, soybean meal, meat meal, whey powder, egg white and beef, etc.) (Sarwar et al, 1983;Elkin, 1984;Spindler et al, 1984;Gehrke et al, 1985;MacDonald et al, 1985;Elkin and Wasynczuk, 1987;Iwaki et al, 1987;Hagen et al, 1989;Cubedo Fernández-Trapiella, 1990;Van Der Meer, 1990) or pure proteins such as casein, ␤-lactoglobulin, lysozyme, etc.) (Sarwar et al, 1983;Bidlingmeyer et al, 1984;Cohen et al, 1984Cohen et al, , 1986Gehrke et al, 1985;MacDonald et al, 1985;Hagen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…(Sarwar et al, 1983;Elkin, 1984;Spindler et al, 1984;Gehrke et al, 1985;MacDonald et al, 1985;Elkin and Wasynczuk, 1987;Iwaki et al, 1987;Hagen et al, 1989;Cubedo Fernández-Trapiella, 1990;Van Der Meer, 1990) or pure proteins such as casein, ␤-lactoglobulin, lysozyme, etc.) (Sarwar et al, 1983;Bidlingmeyer et al, 1984;Cohen et al, 1984Cohen et al, , 1986Gehrke et al, 1985;MacDonald et al, 1985;Hagen et al, 1989). Very few studies have been reported on milk (Hanning et al, 1992) and infant formula (Sarwar et al, 1988(Sarwar et al, , 1989Astephen and Wheat, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation